Penyusunan dan Analisis KKP atas Akun Kas Dalam Pemeriksaan Akuntansi: Studi Berbasi Praktik diKantor Akuntan - Rhida Arsy Farah Diba; Gideon Setyo Budiwitjaksono (Forum Kerjasama Pendidikan Tinggi, 2026)
This study examines the preparation and analysis of Cash Account Audit Working Papers (KKP) based on an internship experience at a Public Accounting Firm (KAP). Cash was selected because it is highly liquid and carries a relatively high risk of material misstatement and fraud, particularly when internal controls are not effectively implemented. Using a descriptive qualitative approach, the study describes the cash audit procedures performed by auditors, including document collection (bank statements, cash receipts/disbursements evidence, and bank confirmations), physical cash testing (petty cash), bank reconciliation preparation, and vouching of transaction evidence. These procedures were documented in the working papers in line with audit documentation and audit evidence principles (SA 230 and SA 500), forming an audit trail that supports senior auditor review. The practical evaluation identified three key findings: (1) weaknesses in transaction documentation, especially the reliance on electronic evidence such as screenshots without sufficient supporting documents; (2) petty cash discrepancies and/or balance differences caused by delayed recording that require tracing and adjustments; and (3) weak authorization over cash disbursements, increasing the risk of unauthorized transactions. In addition, the cash audit must be understood across cycles due to its linkage with revenue, receivables/payables, and operating cash flows, supporting analysis within an integrated accounting system. These findings imply the need to strengthen internal controls—particularly authorization, timely recording, and standards for validating digital evidence—to improve the reliability of cash account audits in the context of audit digitalization..